Synthesis and Biological Evaluation of β-Phenylalanine Derivatives Containing Sulphonamide and Azole Moieties as Antiproliferative Candidates in Lung Cancer Models - Vytautas Mickevičius; Kazimieras Anusevičius; Birutė Sapijanskaitė-Banevič; Ilona Jonuškienė; Linas Kapočius; Birutė Grybaitė; Ramunė Grigalevičiūtė; Povilas Kavaliauskas (Molecules)
In this study, a series of novel β-phenylalanine derivatives were synthesised and evaluated for their anticancer activity. The 3-(4-methylbenzene-1-sulfonamido)-3-phenylpropanoic acid (2) was prepared using β-phenylalanine as a core scaffold. The β-amino acid derivative 2 was converted to the corresponding hydrazide 4, which enabled the development of structurally diverse heterocyclic derivatives including pyrrole 5, pyrazole 6, thiadiazole 8, oxadiazole 11, triazoles 9 and 12 with Schiff base analogues 13 and series1,2,4-triazolo [3,4-b][1,3,4]thiadiazines 14. These modifications were designed to enhance chemical stability, solubility, and biological activity. All compounds were initially screened for cytotoxicity against the A549 human lung adenocarcinoma cell line, identifying N-[3-(3,5-dimethyl-1H-pyrazol-1-yl)-3-oxo-1-phenylpropyl]-4-methylbenzenesulfonamide (5) and (E)-N-{2-[4-[(4-chlorobenzylidene)amino]-5-thioxo-4,5-dihydro-1H-1,2,4-triazol-3-yl]-1-phenylethyl}-4-methylbenzenesulfonamide (13b) as the most active. The two lead candidates were further evaluated in H69 and H69AR small cell lung cancer lines to assess activity in drug-sensitive and multidrug-resistant models. Schiff base 13b containing a 4-chlorophenyl moiety, retained potent antiproliferative activity in both H69 and H69AR cells, comparable to cisplatin, while compound 5 lost efficacy in the resistant phenotype. These findings suggest Schiff base derivative 13b may overcome drug resistance mechanisms, a limitation commonly encountered with standard chemotherapeutics such as doxorubicin. These results demonstrate the potential role of β-phenylalanine derivatives, azole-containing sulphonamides, as promising scaffolds for the development of novel anticancer agents, particularly in the context of lung cancer and drug-resistant tumours.